The Role of Tunjung Nyaho Art and Culture Studio in the Preservation of Karungut Art in Palangka Raya City, Central Kalimantan - Wafa, Itmamil; Rochgiyanti, Rochgiyanti; Mansyur, Mansyur (Universitas Syiah Kuala, 2025)
Karungut art is one of the traditional art forms that is currently facing various challenges in its preservation. This is due to the development of modern arts and the lack of support for the development of traditional arts. This research examines how the Tunjung Nyaho Art and Culture Studio plays a role in preserving Karungut art. The research used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation of studio activities. Data analysis used the Miles and Huberman interactive analysis model which includes data reduction to select important information related to the role of the studio, data presentation in the form of narrative descriptions of preservation efforts, and conclusions that are verified continuously during the research. The results showed that the studio has made various preservation efforts through socialization to the community, fostering the next generation, organizing routine exercises, and conducting art creativity competitions. Tunjung Nyaho Art and Culture Studio proved to have an important role in maintaining the existence of Karungut art in Palangka Raya, Central Kalimantan. In addition, this studio also functions as a gathering place and practice to preserve Ngaju Dayak culture, especially Karungut art, so that it survives and is increasingly recognized by the community.